Characterisation of non-exhaust emissions from road traffic in Lisbon. (1st October 2022) - Cunha-Lopes, I.; Alves, C.A.; Casotti Rienda, I.; Faria, T.; Lucarelli, F.; Querol, X.; Amato, F.; Almeida, S.M.
Abstract: Non-exhaust emissions from road transport include particles from brake and tyre wear, road surface abrasion and dust resuspension. Road dust loads and their chemical properties are heterogeneous and their knowledge is still scarce. This study aimed to characterise, for the first time in Lisbon, the thoracic fraction of road dust (PM10 ) by collecting samples directly from road pavements by an in situ resuspension chamber. The highest PM10 load (15.6 ± 8.75 mg m −2 ) was obtained on a cobblestone pavement, while for asphalt roads the mean PM10 load was 4.40 ± 0.16 mg m −2 . Emission factors for asphalt pavements ranged from 83.5 to 274 mg veh −1  km −1 . On average, 65.7% of the PM10 mass was reconstructed, taking into account the carbonaceous content and the sum of the elements in their oxidized form. Cu and Zn, associated with brake and tyre wear, were the most enriched elements in relation to the soil composition ( EnF = 440 and 184, respectively). The highest potential ecological risk factor of individual metals ( Eri ) was also observed for Cu ( Eri Cu  = 393). In 90% of the sampled streets, the total carcinogenic risk was higher than 1E-4 for As, suggesting that exposure to this hazardous element may contribute to the development of cancer over a lifetime. The results showed the high contribution of certain dangerous chemical compounds associated with resuspension particles and their potential effects on human health. Graphical abstract: Image 1 Highlights: Non-exhaust emissions have an important impact on the environment and health. Cobbled pavement had a higher dust load than asphalt pavements. Cu revealed the highest potential ecological harmful effect. Cu and Zn revealed an extremely high pollution index in all road sampling sites. Exposure to As may contribute to the development of cancer over a lifetime.